THE INFLUENCE OF MOTIVATION, PERSONALITY AND ATTITUDE ON ACADEMIC DISHONESTY STUDENTS OF SMKN 12 JAKARTA - Adinda Putri Mustafa; Tuty Sariwulan; Widya Parimita (PT. Hasba Edukasi Mandiri, 2025)
The research entitled The Influence of Motivation, Personality, and Attitude towards Academic Dishonesty has the aim of knowing how the influence of Motivation, Personality, and Attitude towards Academic Dishonesty Students of SMKN 12 Jakarta with a total sample of 87 students. The research method uses quantitative research with multiple regression analysis and data collection techniques conducted online through questionnaires. The results of the study revealed that motivation had a significant effect on academic dishonesty with a t-test value of 4.018 > t-table 1.66342. Second, personality has a significant effect on academic dishonesty with a t-test value of 1.666 > t-table 1.66342. Third, attitude has a significant effect on academic dishonesty with a t-test value of 2.218 > t-table 1.66342. Fourth, Motivation, Personality and Attitude have a significant effect on academic dishonesty with an f-test value of 4584.58 > f table 1.66.